Invited examiner of PhD dissertations : Elena Vichi (Sant’ Anna School of Advanced Studies), External examiner of the dissertation Title: The effects of Zinc, Caffeine and NaCl on olive and tomato physiology and metabolism Advisors: Luca Sebastiani - Manganaris, George A. (My University, 2026)
Invited examiner of PhD dissertations.
Keywords: Sciences